Anaphylactic Shock at the End of Hemodialysis. Issue 6 (4th July 2015) - Aziz, Nivin; Luna, Carla; Mirza, Farheen; Tobin, Mary
Abstract: Allergic reactions to epoetin alfa, including anaphylaxis, have been described but desensitization in the setting of an IgE‐mediated reaction has not been reported. We present a case of a hemodialysis patient who developed symptoms of an IgE‐mediated allergic response to epoetin alfa that occurred after each administration. These reactions progressed to a single episode of anaphylaxis with generalized pruritus, urticaria, oropharyngeal edema, and hypotension that prompted its discontinuation. Intradermal skin testing confirmed an allergic response to this agent. The patient then underwent a desensitization procedure to epoetin alpha after which she was able to tolerate it without further problems.